Strategies Australian junior doctors use to maintain their mental, physical and social well-being: a qualitative study - Melanie Hobi; Sonya Yegorova-Lee; Christopher Chun-lin Chan; Hailin Zhao; Stephen Jiang; Dan Tran; Gayathri Nair; Erika Borkoles (BMJ Open)
Objectives This study aimed to uncover the strategies that junior doctors implement to maintain their mental, physical and social well-being, and the barriers they experience in practising these strategies.Participants Fifteen junior doctors in their postgraduate year 1 or 2 currently practising in Australia were recruited.Outcome measures Semistructured interviews were conducted, and the transcripts underwent thematic analysis.Results Three key themes emerged from thematic analysis, namely: well-being strategies, barriers to well-being and and future interventions. Exercise, a healthy and balanced diet, quality sleep, and workplace organisations were frequently reported well-being strategies. High workload, unpredictable routines, lack of familiarity with the healthcare system and ongoing stigma surrounding mental health were seen as barriers to well-being. Suggested interventions included increased control over rosters, subsidised access to facilities such as gyms and increased internship preparedness programmes organised by the medical schools.Conclusions The findings from this study may assist in developing more personalised and targeted methods to help junior doctors maintain their mental, physical and social well-being. Future studies may address the structural and systemic changes required to develop a workforce that fosters the well-being of junior doctors and reduces the institutional barriers to practising well-being strategies.